Teeth as an Indicator of the Environmental Exposure of Silesia Province’s Inhabitants in Poland to Metallic Trace Elements - Joanna Domagalska; Małgorzata Ćwieląg-Drabek; Grzegorz Dziubanek; Natalia Ulatowska; Sylwia Bortlik; Agata Piekut (Toxics, 2024)
(1) Background: The elemental composition of teeth can provide an estimate of environmental exposure to heavy metals. The aim of this study was to analyze the possibility of using teeth in the biomonitoring of environmental exposure to heavy metals as an indicator of contaminants present in the human residential environment. (2) Methods: The research materials were 110 samples of extracted teeth. The samples were taken from people living in three areas in the province of Silesia. The concentrations of cadmium, lead, and mercury in the samples were determined. (3) Results: The results of the chemical analysis of the collected samples showed a significant variation in the concentrations of heavy metals (Cd, Pb, and Hg) in the analyzed teeth. Furthermore, the mean concentrations of the analyzed heavy metals in the teeth varied according to the patient’s place of residence, the type of tooth analyzed, the presence of caries in the patient, and the smoking or non-smoking status of the patient. (4) Conclusions: The results of the chemical analysis of the teeth of inhabitants of three cities in the most polluted region of Poland indicate that they can be used as an indicator of environmental exposure to cadmium, lead, and mercury.